Procedimiento para la mejora continua de la gestión de recursos humanos - Gemar, Germán; Negrón-González, Ana M; Lozano-Piedrahita, Carlos J; Guzmán-Parra, Vanesa F; Rosado, Norberto (Ingenieria e Investigacion, 2020)
The hotel sector in the historic center of Havana reveals deficiencies in customer satisfaction regarding human resource. This research is aimed at analyzing the results of the implementation of a continuous improvement of human resource management that allows the enhancement of services quality, assuming the Cuban norm. The main results show that 55 % of the items identified with the application of the SERVQUAL model show quality deficit associated with processes of human resource management, such as work competences and work organization. The main dysfunctions identified were unproductive times due to organizational and technical issues and labor fluctuation. Subsequently, hidden costs due to deficiencies were calculated, which amount to a value of 13 249,89 MU/year. To monitor these problems, objectives and indicators are proposed through the Integral Command Table, as well as a plan of corrective and preventive actions.
Procedure for the continuous improvement of human resource management
El sector hotelero en el centro histórico de La Habana revela deficiencias de satisfacción del cliente en relación con los recursos humanos. Esta investigación tiene como objetivo analizar los resultados de la implementación de una mejora continua de la gestión de los recursos humanos que permite mejorar la calidad de los servicios, asumiendo la norma cubana. Los principales resultados muestran que el 55% de los ítems identificados con la aplicación del modelo SERVQUAL reflejan un déficit de calidad asociado a los procesos de gestión de recursos humanos, como las competencias laborales y la organización del trabajo. Las principales deficiencias encontradas son los tiempos improductivos debido a problemas técnicos y organizacionales y la fluctuación laboral. Posteriormente, se calcularon los costos ocultos generados por los disfuncionamientos existentes, los cuáles ascienden a un valor de 13 249,89 MU / año. Para monitorear estos problemas, los objetivos e indicadores se proponen a través de la Tabla de Comando Integral, así como un plan de acciones correctivas y preventivas.
Keywords: dysfunctions; hidden cost; indicators; process; Scopus